2003
DOI: 10.1046/j.1399-3054.2003.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expressed rice ADP‐ribosylation factor 1 (RARF1) induces pathogenesis‐related genes and pathogen resistance in tobacco plants

Abstract: A cDNA encoding RARF1 (rice ADP-ribosylation factor 1) was isolated from fungal elicitor-treated rice suspension culture cells by mRNA differential display. RARF1 transcripts accumulated in response to hydrogen peroxide (H 2 O 2 ) and salicylic acid (SA) and rapidly in cells inoculated with an avirulent pathogen. Constitutively over-expressed RARF1 under the control of the cauliflower mosaic virus 35S promo-ter (CaMV 35S) triggered spontaneous induction of lesion mimics, induced an array of pathogenosis-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Constitutive overexpression of RARF1 in N. tabacum triggered the formation of spontaneous lesions, induced pathogenesis‐related genes and resulted in increased resistance towards the oomycete pathogen Phytophthora parasitica var. nicotianae (Lee et al ., 2003). However, the authors did not suggest a possible molecular mechanism to explain these observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive overexpression of RARF1 in N. tabacum triggered the formation of spontaneous lesions, induced pathogenesis‐related genes and resulted in increased resistance towards the oomycete pathogen Phytophthora parasitica var. nicotianae (Lee et al ., 2003). However, the authors did not suggest a possible molecular mechanism to explain these observations.…”
Section: Discussionmentioning
confidence: 99%
“…(2006) reported that the Arabidopsis ARF-GEF AtMIN7 is specifically targeted by HopM1, a Pseudomonas syringae virulence factor. However, to our knowledge, a direct association of ARF1 with disease response in plants has been reported only once for a rice ARF1: RARF1 (Lee et al ., 2003). Although the authors did not report any loss-of-function data, they showed a rapid pathogen-induced increase in gene expression of RARF1.…”
Section: Introductionmentioning
confidence: 93%
“…, 2004). A notable aspect of plant ARF proteins is a clear involvement of OsARF1 in plant defense, enhancing disease resistance against pathogens with concomitant induction of SA‐activated PR genes (Lee et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…, 2002). Rice ARF was suggested to be involved in disease response, as shown by analyses of transgenic tobacco plants that exhibited fungal pathogen resistance and rapid increase of pathogen‐responsive gene expression (Lee et al. , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we identified an ADP‐ribosylation factor (ARF) which is a member of a multigene family of 20 kDa guanine nucleotide binding proteins (Moss & Vaughan, 1999; Lee et al., 2003), and is also therefore likely to be involved in signal transduction pathways. ARFs are components of various plant defence signalling pathways involved in the induction of expression of a subset of PR genes (Lee et al., 2003) or are assumed to have key biological functions in defensive cytotoxicity, pathogenicity, intracellular signalling, DNA repair, and cell division (Han et al., 1999). They were also found to be differentially expressed in rice cells treated with a fungal elicitor prepared from the rice blast fungus Magnaporthe grisea (T.T.…”
Section: Discussionmentioning
confidence: 99%